PHONOLOGICAL INTERFERENCE IN THE ENGLISH PRONUNCIATION - Muhyidin, Mohammad (IAIN Kediri, 2016)
This study is aimed to know the kinds of phonological interference happen on the English pronunciation of the students of an elementary school in Kediri, East Java. The data were collected by asking the students to read a passage, and this activity was audio-recorded. The data were analyzed by using descriptive qualitative on content analysis. The result of the analysis showed that the phonological interference on the English pronunciation of the students was influenced by their Indonesian language system. It was found nineteen types of interference on the segmental aspects which consisted of nine vowel substitutions, two vowel shortenings and four consonant substitutions, two deletions of consonants and two additions of consonants. On the suprasegmental aspect (stress) there weretwenty misplaced stresses.Keywords;Phonological interference, segmental, suprasegmental.